Legal Certainty Over Ownership Certificates of Building Buildings of Apartment Units Based on Law No. 20 of 2011 Concerning Apartment Houses. 20 of 2011 on Flats - Ni Luh Wiwik Sariani; Erikson Sihotang; Komang Edy Dharma Saputra (Pusat Publikasi Nusantara, 2024)
Legal certainty in property ownership is crucial for protecting the rights and interests of property owners. This study examines the legal certainty provided by ownership certificates for flats under Indonesia's